2008
DOI: 10.1158/1541-7786.mcr-07-0386
|View full text |Cite
|
Sign up to set email alerts
|

FLICE-Like Inhibitory Protein Blocks Transforming Growth Factor β1–Induced Caspase Activation and Apoptosis in Prostate Epithelial Cells

Abstract: Androgen withdrawal induces the regression of human prostate cancers, but such cancers eventually become androgen-independent and metastasize. Thus, deciphering the mechanism of androgen withdrawalinduced apoptosis is critical to designing new therapies for prostate cancer. Previously, we showed that in the rat, castration-induced apoptosis is accompanied by a reduction in the expression of the apical caspase inhibitor FLICE-like inhibitory protein (FLIP). To test the functional role of FLIP in inhibiting pros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 61 publications
(63 reference statements)
4
24
0
Order By: Relevance
“…3). Interestingly, we observed that insulin 108 (likely acting via the IGF-1 receptor 123 ) can block the effect of TGFβ on FLIP expression, consistent with the antagonistic roles of TGFβ and IGF-1 in AWIA.…”
Section: Flip Transcription Is Downregulated In Awiasupporting
confidence: 79%
See 4 more Smart Citations
“…3). Interestingly, we observed that insulin 108 (likely acting via the IGF-1 receptor 123 ) can block the effect of TGFβ on FLIP expression, consistent with the antagonistic roles of TGFβ and IGF-1 in AWIA.…”
Section: Flip Transcription Is Downregulated In Awiasupporting
confidence: 79%
“…116 We found that TGFβ decreased both FLIP mRNA and protein, similar to the effects of androgen withdrawal. 108 NRP-152 cells overexpressing FLIP were resistant to TGFβ induced apoptosis, while siRNA directed against FLIP induced apoptosis, even in the absence of TGFβ. 108 These data indicate that FLIP can directly regulate prostate epithelial cell apoptosis in vitro.…”
Section: Flip Transcription Is Downregulated In Awiamentioning
confidence: 96%
See 3 more Smart Citations